PENGARUH ANTIBAKTERI SEDIAAN SABUN WAJAH CAIR EKSTRAK ETANOL DAUN BELIMBING WULUH (Averrhoa bilimbi L) TERHADAP Staphylococcus aureus METODE DIFUSI - Tumpuk, Sri; Suriansih, Suriansih; Nurhayati, Etiek (poltekkes kemenkes pontianak, 2024)
Facial soap used to clean the face from exposure to dust, pollution, dirt, reduce sebum on the face and eradicate bacteria that can cause acne. Star fruit leaves are efficacious in healing several diseases, such as purulent skin inflammation, boils and medicine for gout. Phytochemical of star fruit leaves contain alkaloid, flavonoid, saponin, tannin and steroid compounds that can inhibit bacterial growth. This study aims to determine the effect of liquid facial soap containing of star fruit leaf extract (Averrhoa bilimbi L) on the growth of Staphylococcus aureus bacteria by diffusion method.This study used a Quasi Experiment research design. The population in this study were wuluh star fruit leaves. The sample used is star fruit leaf extract which is made into liquid facial soap preparations with concentrations of 5%, 10%, 15% and 20%. This antibacterial testing method uses the Kirby-Bauer diffusion method. The results of antibacterial research obtained the average diameter of the inhibition zone at 5% concentration of 10.60 mm, 10% concentration of 11.20 mm, 15% concentration of 12.10 mm, and 20% concentration of 13.23 mm. Based on the diameter of the inhibition zone formed at concentration of 5% is categorized as a moderate response and at concentration of 10%, 15% and 20% is categorized as a strong response.The results of simple linear regression statistical analysis obtained p value = 0.000 < α 0.05 which means Ha is accepted, which means that there is a significant effect on the preparation liquid facial soap ethanol extract of star fruit leaves (Averrhoa bilimbi L) against the growth of Staphylococcus aureus diffusion method.